J. R. R. Tolkien, The Lord of the Rings - Monteiro, Maria do Rosario (2019)
This book presents an analysis of the Lord of the Rings, having as main the transformation that characters suffer due to their different quests. The theoretical background is the use of Jungian psychology applied to myth and psychological transformation. The is the outcome of my Master dissertation in Comparative Literature